Lysine-specific demethylase 1 controls key OSCC preneoplasia inducer STAT3 through CDK7 phosphorylation during oncogenic progression and immunosuppression - Amit Kumar Chakraborty; Rajnikant Dilip Raut; Kisa Iqbal; Chumki Choudhury; Thabet Alhousami; Sami Chogle; Alexa S. Acosta; Lana Fagman; Kelly Deabold; Marilia Takada; Bikash Sahay; Vikas Kumar; et al. (International Journal of Oral Science)
Abstract Oral squamous cell carcinoma (OSCC) progresses from preneoplastic precursors via genetic and epigenetic alterations. Previous studies have focused on the treatment of terminally developed OSCC. However, the role of epigenetic regulators as therapeutic targets during the transition from preneoplastic precursors to OSCC has not been well studied. Our study identified lysine-specific demethylase 1 (LSD1) as a crucial promoter of OSCC, demonstrating that its knockout or pharmacological inhibition in mice reversed OSCC preneoplasia. LSD1 inhibition by SP2509 disrupted cell cycle, reduced immunosuppression, and enhanced CD4+ and CD8+ T-cell infiltration. In a feline model of spontaneous OSCC, a clinical LSD1 inhibitor (Seclidemstat or SP2577) was found to be safe and effectively inhibit the STAT3 network. Mechanistic studies revealed that LSD1 drives OSCC progression through STAT3 signaling, which is regulated by phosphorylation of the cell cycle mediator CDK7 and immunosuppressive CTLA4. Notably, LSD1 inhibition reduced the phosphorylation of CDK7 at Tyr170 and eIF4B at Ser422, offering insights into a novel mechanism by which LSD1 regulates the preneoplastic-to-OSCC transition. This study provides a deeper understanding of OSCC progression and highlights LSD1 as a potential therapeutic target for controlling OSCC progression from preneoplastic lesions.